2022
DOI: 10.1128/jb.00082-22
|View full text |Cite
|
Sign up to set email alerts
|

ThioredoxinA1 Controls the Oxidative Stress Response of Francisella tularensis Live Vaccine Strain (LVS)

Abstract: The role of thioredoxins in the oxidative stress response of F. tularensis is not known. This study demonstrates that of the two thioredoxins, TrxA1 is vital to counter the oxidative stress in F. tularensis live vaccine strain (LVS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Together, these results indicate that thioredoxin gene trxA1 is required for virulence in F. novicida and in intramacrophage infection. A recent study confirmed that in F. tularensis LVS, trxA1 (FTL_0611) but not trxA2 (FTL_1224) plays a major role in the oxidative stress response ( Ma et al., 2022 ). A second thioredoxin gene trxA2 is also present in the genome and may have a role in protecting against oxidative stress resistance over long periods of time ( Ma et al., 2022 ; Ma et al., 2019 ).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Together, these results indicate that thioredoxin gene trxA1 is required for virulence in F. novicida and in intramacrophage infection. A recent study confirmed that in F. tularensis LVS, trxA1 (FTL_0611) but not trxA2 (FTL_1224) plays a major role in the oxidative stress response ( Ma et al., 2022 ). A second thioredoxin gene trxA2 is also present in the genome and may have a role in protecting against oxidative stress resistance over long periods of time ( Ma et al., 2022 ; Ma et al., 2019 ).…”
Section: Introductionmentioning
confidence: 81%
“…A recent study confirmed that in F. tularensis LVS, trxA1 (FTL_0611) but not trxA2 (FTL_1224) plays a major role in the oxidative stress response ( Ma et al., 2022 ). A second thioredoxin gene trxA2 is also present in the genome and may have a role in protecting against oxidative stress resistance over long periods of time ( Ma et al., 2022 ; Ma et al., 2019 ). Interestingly, it has been proposed that the TrxR-Trx systems may be a target for antibiotic development in some bacteria ( Lu and Holmgren, 2014 ).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations